2020
DOI: 10.1080/10926488.2020.1794319
|View full text |Cite
|
Sign up to set email alerts
|

Power, Gender, and Individual Differences in Spatial Metaphor: The Role of Perceptual Stereotypes and Language Statistics

Abstract: English speakers use vertical language to talk about power, such as when speaking of people being "at the bottom of the social hierarchy" or "rising to the top".Experimental research has shown that people automatically associate higher spatial positions with more powerful social groups, such as doctors and army generals, compared to lower spatial positions, which are associated with relatively less powerful groups, such as nurses and soldiers. However, power as a social dimension is also associated with gender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Indeed, recent lines of empirical research have begun to yield evidence that metaphors are understood differently by different people. For instance, gender may play a role in influencing people’s perceptions of power metaphors, with one study finding that male participants were faster to identify powerful groups when they were labeled as male and presented at the top of a computer screen ( Winter et al, 2020 ; see also Charteris-Black, 2012 ; Pérez-Sobrino et al, 2021 ). Handedness may also play a role in metaphoric reasoning: right-handers have been found to make more favorable judgments about objects that are presented on their right-hand side, while left-handers have been found to display more favorable judgments about those presented on their left-hand side ( Casasanto, 2009a ; see also Casasanto and Jasmin, 2010 ; Casasanto and Henetz, 2012 ; but see Sasaki et al, 2019 for contrasting findings in Japanese).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent lines of empirical research have begun to yield evidence that metaphors are understood differently by different people. For instance, gender may play a role in influencing people’s perceptions of power metaphors, with one study finding that male participants were faster to identify powerful groups when they were labeled as male and presented at the top of a computer screen ( Winter et al, 2020 ; see also Charteris-Black, 2012 ; Pérez-Sobrino et al, 2021 ). Handedness may also play a role in metaphoric reasoning: right-handers have been found to make more favorable judgments about objects that are presented on their right-hand side, while left-handers have been found to display more favorable judgments about those presented on their left-hand side ( Casasanto, 2009a ; see also Casasanto and Jasmin, 2010 ; Casasanto and Henetz, 2012 ; but see Sasaki et al, 2019 for contrasting findings in Japanese).…”
Section: Introductionmentioning
confidence: 99%
“…It is consistently shown that the meanings of metaphors and images are highly subjective and contextual ( ño, 2020 ; Pink, 2011 ; Winter et al, 2020 ). Existing research that incorporates the perspectives of people affected by dementia currently focuses upon researchers’ analyses of people’s verbal or written metaphorical expressions ( Brown Wilson et al, 2021 ; Castaño, 2020 ; Golden et al, 2012 ; Johannessen et al, 2015 ; Peel & Harding, 2014 ; Thorsen & Johannessen, 2021 ; Zimmermann, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to height perception, studies have shown that tall males are deemed to be more "masculine" (Griffith, 2017), of higher status (Stulpet al, 2013;Phillip, 2014), capable and competent (Thompson, 2014;Re, 2013;Watkins et al, 2010;Winter et al, 2020;Bittman, 2019;Murray and Schmitz, 2011), dominant and assertive (Re et al, 2013;Schmitz and Murray, 2017;Olivola and Todorov, 2010;Valentova et al, 2014), and respected and feared by potential opponents (Lewis et al, 2013). Height in males has also been positively correlated with cognitive abilities (Bittman, 2019;Adonis, 2011;Kobayashiet al, 2018), and social and financial success (Phillip, 2014;Bittman, 2019;Bargain and Zeidan, 2017;Adonis, 2011).…”
Section: Introductionmentioning
confidence: 99%